Intelligent tuning and adaptive control : selected papers from the IFAC Symposium, Singapore, 15-17 January 1991 - Devanathan, R. (Rajagopalan) (IFAC symposia series, 1991)
This volume contains 67 papers reporting on the state-of-the-art research in the fields of adaptive control and intelligent tuning. Papers include applications in robotics, the processing industries and machine control.